Enhancing bioremediation efficiency of acidic wetlands contaminated with crude oil. - Jumbo, Raphael Butler (Cranfield University, 2023)
Crude oil exploration and exploitation has significantly impacted the Niger Delta, Nigeria wetlands and its ecosystems. Studies suggest that acidification is ongoing with several acid forming and acid tolerant microbes identified in the Niger Delta wetlands. The efficient remediation of the crude oil contaminants in the acidified wetlands is the only alternative left to the Niger Delta for effective ecological restoration of the environment. In this research, different combinations of bioremediation strategies were investigated to enhance the remediation of simulated crude oil contaminated acidic wetlands similar to the Nigeria Niger Delta wetlands contamination conditions. A series of mesocosm experiments subjected to wetland condition and a combination of treatments were evaluated as follows: for biostimulation experiment, Food waste anaerobic digestate (FWAD), and Tween 80 surfactant were individually added to the mesocosms at 10%, 20% and 30% w/w respectively with soil in the mesocosm experiments. For bioaugmentation experiments, mesocosms were enriched with Pseudomonas aeruginosa, Bacillus subtilis, or microbes indigenous to the crude oil spiked soil. Sequel to the results of these experiments, an optimised combination of FWAD (30% w/w) plus Tween 80 (30% w/w), Tween 80 (30% w/w) plus indigenous microbes, and digestate (30% w/w) plus Tween 80 (30% w/w) plus indigenous microbes were investigated. For each set of the experiments, pristine soil, acidified soil, and crude oil spiked acidified soil were maintained as controls. Total petroleum hydrocarbon (TPH) contents, soil basal respiration, and soil microbial communities’ dynamics were measured over 112 days of the experiments. For the biostimulation experiment, the FWAD and Tween 80 each at 30% (w/w) resulted in the highest petroleum hydrocarbons degradation (> 87% removal in 49 days). Augmentation with indigenous microbes enhanced the extent of degradation of the petroleum hydrocarbons (up to 80% in 49 days). For the optimised combined strategies, digestate (30% w/w) plus Tween 80 (30% w/w) plus indigenous microbes resulted in degradation of the hydrocarbons by > 98%. The correlation between basal respiration, microbial community and hydrocarbons showed that the more the biogenic CO₂ produced by the relevant microbial community, the faster the rate of the hydrocarbons degradation. Gram positive bacteria were the dominant microbial group in the FWAD, Tween 80 surfactant, indigenous microbes, and combined digestate (30% w/w) plus Tween 80 (30% w/w) plus indigenous microbe mesocosms. This research has demonstrated that acidified wetlands contaminated by petroleum hydrocarbons can be effectively remediated using low carbon biomaterials and indigenous microbial consortia. This conclusion was further confirmed by the more than 90% maize germination and undetectable bioavailable hydrocarbons recorded at the end of the experiment in these mesocosms. Potential exists for further studies in low carbon remediation of weathered hydrocarbons contaminants in various types of wetlands and sediments using FWAD, Tween 80 surfactant, and indigenous microbes.
Bortone, Imma - Associate Supervisor Coulon, Frederic - Associate Supervisor
Keywords: Bioremediation; wetlands; hydrocarbons; microbes; digestate; remediation